Pengembangan Teknologi Pengolahan Gula Aren Bagi Kelompok Tani di Desa Cisolok Kabupaten Sukabumi - Rahaju, Sri Mumpuni Ngesti; Marlin, Syamsu; Wiradinata, Trisna Ardi; Sugiyanto, Didik (Jurnal Pengabdian Masyarakat Singa Podium (JPMSIPO), 2023)
The object of Community Service is the Palm Sugar Farmers Group, Cisolok Village, Cisolok District, Sukabumi Regency. Where the farmer group is under the management of the Binekas Cooperative, in this activity partners are able to take part in the entire process of the Community Service Program starting from describing problems, finding solutions, planning and implementing the entire program as well as being able to socialize the results of technology application to all group members and are ready to contribute to in-kind funding for implementation Community Service Program. Problems for the Palm Sugar Farmers Group, Cisolok Village, Cisolok District, Sukabumi Regency, the first in the field of production in processing palm sugar from plantations still using traditional methods. The aim of the first activity is how to solve problems related to the production process, especially in the palm sugar crystallization process. and sieving it into ant sugar. The second objective is to improve marketing management, especially in the field of packaging that is attractive to consumers and create standard packaging for palm sugar and increase consumer knowledge through online product sales. As a result of community service activities, there has been an increase in processing with the crystallization machine and sieving of palm sugar into powdered sugar or ant sugar, from a marketing perspective there has been a further increase in broader marketing methods via the internet.